Anatomopathological Evaluation of Fecal Peritonitis Complications in Horses Treated with Peritoneal Lavage - Fernandes Silva, Thiago Jhonatha; Dória, Renata Gebara Sampaio; Félix da Silva, Waldelucy Karina Bomfim; Grigoletto, Renan; Ginelli, Antônio Marcos Guimarães; Escodro, Pierre Barnabé; e Oliveira, Natalia Franco de Oliveira (Acta Scientiae Veterinariae, 2018)
Background: Reproductive management in horses when performed with malpractice or by an unqualified person can cause many lesions of various degrees. When the rectum is affected it can compromise the mucous layer of the rectal ampulla and may even cause total perforation of this intestinal segment. Once the rectum ruptured, its contents gets into the abdominal cavity and generates severe abdominal infection, which may cause intense adhesions between organs and even to the abdominal wall and requires a particular intensive intervention. This work reports the use of peritoneal lavage protocol in three horses with septic peritonitis caused by rectal laceration, correlating with post-mortem findings. Cases: Three horses were referred to the Veterinary Hospital Rancho Belo Vista, in the city of Serra - ES, with an accident report during reproductive management in different properties. In all cases, blood loss and loss of continuity of the rectal mucosa were reported by the technicians. Patients were referred at different post-accident times. When they arrived at the hospital, they were examined and a sample of blood and peritoneal fluid were collected and sent to the laboratory. They presented intense apathy, mucosa coloration ranging from hyperemic to pale with halo toxemia, high cardiac and respiratory rate, reduction of globular volume and prolonged time of capillary refill. Patients were given fluid therapy support with lactated Ringer’s solution and systemic therapy protocols such as antibiotic therapy, peritoneal lavage with antibiotic containing solution and anticoagulant, and other supportive treatments were instituted. Peritoneal lavages were instituted every eight hours, in the first 48 hours and every twelve hours, until five days were completed. All patients had to be sacrificed. Euthanasia occurred at different times according to response to treatment and onset of clinical signs of shock. Significant variations were observed among patients at necropsy. The patient submitted to fewer wash cycles had severe adhesions. The other two patients who underwent more wash cycles presented less severe adhesion and less fibrin deposition in the abdominal viscera. Discussion: The use of peritoneal lavage associated with systemic treatment has been shown to be beneficial for the treatment of peritonitis since the initial condition and alteration in the results of laboratory tests. However, the time elapsed between rectal laceration and referral to a specialized technical unit was a decisive factor, together with the severity of the lesion, that were determinant for the increased response and consequent chance of treatment success and chances of survival. Although they received a combination of systemic therapy with broad-spectrum antibiotics and peritoneal lavage associated with daily washing cycles, the patients were euthanized, reiterating the lethality of the disease. At necropsy it was possible to evaluate the extent of contamination and adhesions, as well as to find the lacerated segment, the main source of contamination of the peritoneum. The difference between the degrees of adhesion is evident when compared to the patients who went through more cycles of peritoneal lavage with the ones that went through fewer cycles. Thus, it is possible to estimate that the patients who received a greater number of peritoneal lavage cycles with the drugs used in the same route presented a reduced number of adhesions between similar structures (same organs) and between the organs and the abdominal wall. There is a need for more controlled studies to evaluate the effectiveness of serial peritoneal lavage treatments in horses, as well as the application of drugs that seek to reduce abdominal inflammation, fibrin production and adhesions.